Sistem Pengatur Sirkulasi Air Otomatis Metode Tanam Hidroponik Menggunakan Tenaga Surya - Alfi Gozali, Achmad; , Hasyim Asy'ari, ST., MT (2016)
Solar power generation system used to convert the sun's light energy into electrical energy, the electrical energy generated can be used to regulate water circulation automated hydroponic growing methods, due to reduced urban land hydroponic cultivation techniques are very suitable for urban communities, to the regulatory system needs to be made of water circulation hydroponic growing methods in order to facilitate the urban community in planting. Designing regulator automatic water circulation hydroponic growing methods use a timer as automatic, solar panels as an energy converter, the charge control as a regulator of the balance of electric current, the inverter as modifiers DC voltage to AC voltage and the motor as the driving force. Automatic control system of water circulation hydroponic growing methods use a timer set for two minutes to turn on the pump. Pump operates three times per day as a driver of water circulation. PLTS ability depends on the intensity of light to generate electric power, on the condition of the current low-value light intensity of 50 lux, a current of 0.6 amperes voltage of 12.3 volts of solar panels to produce power of 7.3 watts, this condition occurs when the afternoons and at peak conditions currently worth 678 lux light intensity, a current of 5.09 amperes, a voltage of 15.7 volts solar panels produce power of 79.9 watts this condition occurs when daylight. The average power per day can only reach 45% of the power indicated on the name plate solar panel condition onion plants grow roots on the fourth day and the leaves begin to grow on the fifth day